Preservice Teachers education - Mayank Sharma; Ramakant Sharma (AG Volumes, 2022)
The education and training that student teachers get before they begin their careers as teachers is referred to as pre-service teacher education and pre-service teacher preparation. Education for instructors prior to their employment as a teacher is known as pre-service education. During this time in teacher education programmes, students are simultaneously learning about theoretical papers and putting their new knowledge into practise. There is a lot of room for improvement in the teacher training programme. Various sorts of instructors are prepared via pre-service education. Courses and experiences in the field are what make up pre-service teacher training. These courses and experiences are not tied to one another. It has yet to take root in pre-service teacher education research-based curriculum creation. These programmes are meant to not only support and promote teacher learning, but also build a better degree of self-confidence in the individuals participating in the programmes. In this situation, new teachers learn from their own experience as well as from the distinct cultures and traditions of the schools in which they are assigned. Students and their instructors will benefit from this paper’s discussion on pre-service teacher education.